Energetics Equivalent of the Cardiac Force-Length End-Systolic Zone: Implications for Contractility and Economy of Contraction - Tran, Kenneth; Taberner, Andrew J.; Loiselle, Denis S.; Han, June-Chiew (Frontiers in Physiology, 2020)
We have recently demonstrated the existence of a region in the cardiac mechanics stress-length plane, which we have designated “The cardiac end-systolic zone”. The zone is defined as the area on the pressure-volume (or stress-length) plane within which all stress-length contraction profiles reach their end systolic points. It is enclosed by three boundaries: the isometric end-systolic relation, the work loop (shortening) end-systolic relation, and the zero-active stress isotonic end-systolic relation. The existence of this zone reflects the contraction mode dependence of the cardiac end-systolic force-length relations, and has been confirmed in a range of cardiac preparations at the whole-heart, tissue and myocyte levels. This finding has led us to speculate that a comparable zone prevails for cardiac metabolism. Specifically, we hypothesise the existence of an equivalent zone on the energetics plane (heat vs stress), and that it can be attributed to the recently-revealed heat of shortening in cardiac muscle. To test these hypotheses, we subjected trabeculae to both isometric contractions and work-loop contractions over wide ranges of preloads and afterloads. We found that the heat-stress relations for work-loop contractions were distinct from those of isometric contractions, mirroring the contraction mode-dependence of the stress-length relation. The zone bounded by these contraction mode-dependent heat-stress relations reflects the heat of shortening. Isoproterenol-induced enhancement of contractility led to proportional increases in the zones on both the mechanics and energetics planes, thereby supporting our hypothesis.